Ab Initio Emulsion Atom‐Transfer Radical Polymerization. (30th May 2018) - Lorandi, Francesca; Wang, Yi; Fantin, Marco; Matyjaszewski, Krzysztof
Abstract: Stable latexes of poly(meth)acrylates with predetermined molecular weights, narrow molecular‐weight distributions, and controlled architecture were prepared by true ab initio emulsion atom‐transfer radical polymerization. Water‐soluble (macro)initiators in combination with a hydrophilic catalyst, Cu/tris(2‐pyridylmethyl)amine, initiated the polymerization in the aqueous phase. The catalyst strongly interacted with the surfactant sodium dodecyl sulfate (SDS), thereby tuning the polymerization within nucleated hydrophobic polymer particles. Long‐term stable latexes were obtained, even with SDS loading below 3 wt % relative to monomer. Block and gradient copolymers were prepared in situ. The reaction volume and solid content were successfully increased to 100 mL and 40 vol %, respectively, thus suggesting facile scale‐up of this technique. The proposed setup could be integrated in existing industrial plants used for emulsion polymerization.